2021
DOI: 10.1097/j.pain.0000000000002266
|View full text |Cite
|
Sign up to set email alerts
|

International Association for the Study of Pain Presidential Task Force on Cannabis and Cannabinoid Analgesia: research agenda on the use of cannabinoids, cannabis, and cannabis-based medicines for pain management

Abstract: The President of the International Association for the Study of Pain established a task force on cannabis and cannabinoid analgesia to systematically examine the evidence on (1) analgesic pharmacology of cannabinoids and preclinical evidence on their efficacy in animal models of injury-related or pathological persistent pain; (2) the clinical efficacy of cannabis, cannabinoids, and cannabis-based medicines for pain; (3) harms related to long-term use of cannabinoids; as well as (4) societal issues and policy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…This necessitates investigation of CBD including dosing regimens and treatment efficacy in different pain conditions in high-quality studies as recently suggested. 21 The aim of this single-centre randomized double-blind placebo-controlled trial was to investigate the analgesic effect and safety of 12-week administration of synthetic CBD as an addon treatment to conventional pain management in patients with hand osteoarthritis (Hand-OA) and psoriatic arthritis (PsA).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This necessitates investigation of CBD including dosing regimens and treatment efficacy in different pain conditions in high-quality studies as recently suggested. 21 The aim of this single-centre randomized double-blind placebo-controlled trial was to investigate the analgesic effect and safety of 12-week administration of synthetic CBD as an addon treatment to conventional pain management in patients with hand osteoarthritis (Hand-OA) and psoriatic arthritis (PsA).…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates investigation of CBD including dosing regimens and treatment efficacy in different pain conditions in high-quality studies as recently suggested. 21…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study lead to a number of additional considerations: Future clinical trials of CbMs for chronic pain should adhere to current protocol guidelines for comprehensive assessment of harms, with explicit reporting of serious adverse events, and quantitative reporting of adverse events using validated methods. 12 More accurate information regarding harms is needed as current epidemiological studies indicate that adults with chronic pain are particularly at risk for adverse cannabis outcomes, mostly, CUD. 13 Although this concerning data on CUD in patients with chronic pain 10 could compromise patient care, some selected patients who may benefit from CbMs and MC should be allowed access with appropriate medical oversight.…”
Section: Discussionmentioning
confidence: 99%
“…The author's conclusion is in direct contrast to the conclusion and recommendations from the International Associations for the Study of Pain (IASP) Cannabis Task Force. Based on a thorough evaluation of current evidence, Rice et al (2021) concluded ‘That the available clinical evidence neither supports nor refutes claims of analgesic efficacy or safety for cannabinoids, cannabis, or cannabis‐based medicines’ and suggested future studies and recommendations should follow rigid rules of conclusive randomized, placebo‐controlled randomized controlled trials (RCTs) to provide evidence (Haroutounian et al, 2021).…”
Section: Reference To Studies With High Quality Of Evidencementioning
confidence: 99%